تقييم جودة العملية التعليمية لقسم المحاسبة وانعكاساتها من وجهة نظر الطلبة: دراسة تطبيقية على قسم المحاسبة / كلية الاقتصاد والمحاسبة / جامعة سبها / ليبيا - حسن إجبارة , عبد المنعم; إبراهيم المهدي , إبراهيم المهدي (مجلة البحوث الأكاديمية, 2018)
The aim of this study is to identify the views of the students on the level of the educational process in the accounting department of the Faculty of Economics and Accounting at the University of Sabha. To achieve the objectives of the study, a questionnaire form was prepared and distributed to a sample of students from the accounting department and students from the other departments who are taught by their professors from the accounting department. The study showed several results, the most important of which is that the quality of the educational process in the accounting department according to the studied elements varies between the high and intermediate levels from the students' point of view. The study has reached several recommendations, the most important of which is the need to deepen and increase the awareness of the culture of the overall quality of the members of the teaching staff, administrative leaders and employees in higher education institutions by training them and informing them about the experiences of international universities and the successes achieved as a result of their adoption of TQM.